Audit committee's chairman characteristics and auditor choice: an empirical evidence from Malaysia ACE market - Esam Mohammed A. Alsayani; Mohamad Naimi Mohamad Nor; Ebrahim Mohammed Al-Matari (Cogent Business & Management, 2023)
Audit quality is a strong external monitoring mechanism to protect the interest of the owners according to agency theory. The auditor choice research has paid more attention to the audit committee overall but has overlooked the unique agency context of audit committee's chairman characteristics on the audit quality especially on auditor choice. Therefore, the purpose of this study is to investigate the audit committee's chairman characteristics on the auditor choice. The sample of 111 firms listed on the ACE market was used to test the hypotheses. Using logistic regression, this study finds that only the audit committee's chairman tenure and busyness are significant factors that influence the auditor choice. Whereas, the audit committee's chairman ethnicity, expertise and qualification have no significant influence on the auditor choice. These results have theoretical implications for the alignment and entrenchment hypotheses of the agency theory and practical implications for the regulators to improve the audit committee's structure and regulations.
Keywords: G34; M42; D25; 650; ACE market Malaysia; Audit committee's chairman characteristics; Auditor choice